RANCANG BANGUN SISTEM ABSENSI SISWA SMKN KAIDIPANG MENGGUNAKAN RFID DAN ESP 8266 BERBASIS WEB - Korompot, Samsul; Tansa, Salmawaty; Wiranto, Ifan; Dako, Amirudin Yunus; Bonok, Zainudin; Nasibu, Iskandar Zulkarnain (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Abstract : Design and Construction of a Kaidipang Vocational School Student Attendance System Using WEB-Based RFID and ESP 8266. This research aims to build a web-based RFID and ESP8266 attendance system. This system uses RFID cards to identify students and store attendance data digitally. The methods used in this research are literature study, observation and experiment. The research results show that the RFID and web-based ESP8266 attendance system can read and process data quickly and accurately, and student attendance is recorded correctly. This system can also operate consistently and does not experience significant disruption. The implementation of an RFID-based and web-based ESP8266 attendance system at SMK Negeri 1 Kaidipang is expected to increase the efficiency and effectiveness of recording student attendance data at SMK 1 Kaidipang, which currently still uses conventional attendance, resulting in time inefficiencies, proneness to loss of absence data, and the use of a lot of paper. and attendance printing costs.